Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1126/science.1127724
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Seismic Tomography Detects Magma Intrusions at Mount Etna

Abstract: The continuous volcanic and seismic activity at Mount Etna makes this volcano an important laboratory for seismological and geophysical studies. We used repeated three-dimensional tomography to detect variations in elastic parameters during different volcanic cycles, before and during the October 2002-January 2003 flank eruption. Well-defined anomalous low P- to S-wave velocity ratio volumes were revealed. Absent during the pre-eruptive period, the anomalies trace the intrusion of volatile-rich (>/=4 weight pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
187
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 21 publications
17
187
0
1
Order By: Relevance
“…Most seismic events occur at depths between 23 and 28 km. This enables favorable illumination of the crustal structures by seismic rays and creates better conditions for tomographic inversion compared to most other volcanoes, for example, Etna (Patanè et al, 2006). It is interesting that the depth distribution of seismicity over time seems to correlate with major eruptions of the Kluchevskoy volcano.…”
Section: Kluchevskoy Volcano Group: Multi-level Feeding Determines Thmentioning
confidence: 94%
“…Most seismic events occur at depths between 23 and 28 km. This enables favorable illumination of the crustal structures by seismic rays and creates better conditions for tomographic inversion compared to most other volcanoes, for example, Etna (Patanè et al, 2006). It is interesting that the depth distribution of seismicity over time seems to correlate with major eruptions of the Kluchevskoy volcano.…”
Section: Kluchevskoy Volcano Group: Multi-level Feeding Determines Thmentioning
confidence: 94%
“…Moreover, recent time-lapse tomography studies of Mt. Etna [Patanè et al, 2006] and Kluchevskoy volcano [Koulakov et al, 2012] have demonstrated that seismic structures may evolve in time to reflect the reallocation of volatiles, partial melt and stress. It is possible that the structure corresponding to the 1992 eruption period reported in Power et al [1998] may be different than that observed in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, repeated seismic tomographies (12) has been used to detect seismic velocity variations within Mount Etna over periods of a few years. This method reveals variations of the internal volcanic structure before and after an eruption.…”
mentioning
confidence: 99%